Chronic exposure to a predator or its scent does not inhibit male–male competition in male mice lacking brain serotonin - Huo, Ying; Fang, Qi; Shi, Yao-Long; Zhang, Yao-Hua; Zhang, Jian-Xu (Frontiers in Behavioral Neuroscience, 2014)
Although it is well-known that defective signaling of the 5-HT system in the brain and stressful stimuli can cause psychological disorders, their combined effects on male–male aggression and sexual attractiveness remain unknown. Our research aimed at examining such effects using tryptophan hydroxylase 2 (Tph2) knockout male mice vs. a rat- or rat scent-based chronic stress model. Tph2+/+ and Tph2−/− male mice were placed individually into the rat home cage (rat), a cage containing soiled rat bedding (rat scent) or a cage containing fresh bedding (control) for 5 h every other day for 56 consecutive days. In Tph2+/+ male mice, rat-exposure decreased male–male aggression and sexual attractiveness of urine odor relative to either rat scent-exposure or control; and rat scent-exposure decreased aggression rather than sexual attractiveness of urine odor compared with control. However, such dose-dependent and long-lasting behavioral inhibitory effects vanished in Tph2−/− male mice. RT-PCR assay further revealed that putative regulatory genes, such as AR, ERα and GluR4 in the prefrontal cortex, and TrkB-Tc and 5-HTR1A in the hippocampus, were down-regulated at the mRNA level in either rat- or rat scent-exposed Tph2+/+ male mice, but partially in the Tph2−/− ones. Hence, we suggest that the dose-dependent and long-lasting inhibitory effects of chronic predator exposure on male–male aggression, sexual attractiveness of urine odor, and mRNA expression of central regulatory genes might be mediated through the 5-HT system in the brain of male mice.